2019
DOI: 10.1093/pubmed/fdz034
|View full text |Cite
|
Sign up to set email alerts
|

The development of the gluten free healthy food basket in Cyprus. Is it affordable among low-income adults diagnosed with celiac disease?

Abstract: Background Gluten free (GF) diets are not only restrictive but also costly. The main aim of this study was to evaluate the acceptability, cost and affordability of a Gluten Free Healthy Food Basket (GFHFB) and further examine whether low-income Cypriots diagnosed with celiac disease (CD) experience food stress. Methods GFΗFBs were constructed for adult women and adult men (±40 years) diagnosed with CD. Feasibility and accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…A study in Cyprus examined that affordability was defined as the Gluten-free Healthy Food Basket (GFΗFB) cost as a percentage of the Guaranteed Minimum Income (GMI). As a result, GFΗFB was 33.6 and 47 euros/month more expensive than the other healthy basket food (Chrysostomou, Andreou, & Andreou, 2019). This makes it difficult for low-income people to spend their income on this food.…”
Section: Income Levelmentioning
confidence: 99%
“…A study in Cyprus examined that affordability was defined as the Gluten-free Healthy Food Basket (GFΗFB) cost as a percentage of the Guaranteed Minimum Income (GMI). As a result, GFΗFB was 33.6 and 47 euros/month more expensive than the other healthy basket food (Chrysostomou, Andreou, & Andreou, 2019). This makes it difficult for low-income people to spend their income on this food.…”
Section: Income Levelmentioning
confidence: 99%
“…In addition, affordability rates for low-income people range accordingly. Better affordability is shown for DHFB, following HFB, and then higher affordability is shown for GDHFB (41•92, 59•54 % for woman and man, respectively) (18,19) .…”
Section: Discussionmentioning
confidence: 94%
“…Particularly, a recent study in Cyprus has shown that for low-income people diagnosed with celiac disease and receiving GMI, the proportion of income that must be spent on GFHFB ranges from around 42 to 60 %. Particularly, GFHFB was 33•6 and 47 Euros/month more expensive compared with HFB for women and men, respectively (19) . Thus, comparing the three food baskets (DHFB, GFHFB, HFB) developed for the Cypriot population, it seems that DHFB is the most cost-efficient nutrition therapy for both household types (142•61/202•93 euros, 201•2/285•8 euros, 168•29/240•51 euros for women and men, respectively).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results are similar to studies internationally and in Australia that have investigated affordability of a gluten-free diet for low-income earners. 12,29 Given our results highlight the risk of unaffordability of empiric elimination diets for some family types, the impact of cost of empiric elimination on adherence and financial reimbursement of allergen foods in this group for long-term compliance should be further explored. Despite these barriers, dietary approaches have been demonstrated to be more costeffective long-term compared to medical management.…”
Section: Discussionmentioning
confidence: 99%